Mycoremediation of sewage sludge and manure with marine fungi for the removal of organic pollutants - Stiebeling, Daniel Akira; Labes, Antje (Frontiers in Marine Science, 2022)
The application of manure and sewage sludge on farmland is one key element in building up soil organic matter and is contributing to soil carbon sequestration. These organic fertilizers are often contaminated with anthropogenic pollutants that can cause serious harm to ecosystems and persist over a long period. Bioremediation approaches have gained attention as clean-up treatment in recent decades due to their cost-effectiveness and environmental friendliness. Besides phytoremediation with plants and bacterial bioremediation, fungi have also been successfully applied for pollution control. While land-based species, especially white-rot fungi, are extensively studied for mycoremediation, fungi from marine environments are underrepresented but show adaptive traits (e.g., halophilic, anaerobic) that are beneficial under certain conditions and may improve the degradation portfolio. This review highlights application examples of marine-derived fungi for organopollutant removal and evaluates the overall future potential of this underexplored group, which might become an interesting extension for remediation of manure and sewage sludges with high osmotic pressure.